(untitled) (Journal of the College of Basic Education, 2023)
The research is concerned with the significance of the maternal instincts in Brecht’s Mother Courage and her Children. The portrait of a female in any society being a mother, a sister, a daughter, or a worker.The image of a woman in general and as a mother in particular as a great influence in life. The mother devotes her life for the demands of her children. Brecht deals with the mother as a business woman and how does she lose her children because of her greed and business.He tries to make his dramatic work as an instrument of a new idea for change